Why does a natural myringostapediopexy cause minimal hearing loss? - Dorji Penjor (Wiley, 2021)
Abstract Natural myringostapediopexy is a result of tympanic membrane retraction with automastoidectomy that causes the tympanic membrane to plaster onto the stapes directly. It causes minimal conductive hearing impairment.